Microbial biotechnology alchemy: Transforming bacterial cellulose into sensing disease- A review - Ali Jawad Akki; Pratheek Jain; Ravindra Kulkarni; Raghavendra Rao Badkillaya; Raghavendra V. Kulkarni; Farhan Zameer; V Raghu Anjanapura; Tejraj M. Aminabhavi (Sensors International)
Biosensors have the potential to revolutionize healthcare by providing rapid and accurate diagnosis of diseases. Biosensors are analytical devices that convert molecular recognition of a target analyte into a measurable signal. Older diagnostic techniques, such as immunoaffinity column assays, fluorometric, and enzyme-linked immunosorbent assays, are laborious, require qualified personnel, and can be time consuming. In contrast, biosensors offer improved accuracy, sustainability, and rapidness due to their ability to detect specific biomarkers with high sensitivity and specificity. The review covers various bacterial cellulose (BC)-based biosensors, from SARS-CoV-2 detection to wearable health monitoring and interaction with human-computer interfaces. BC's integration into ionic thermoelectric hydrogels for wearable health monitoring shows its potential for real-time health tracking. Incorporating BC in biosensors for low-noise electrodes, and wearable sensors has been elaborated. The invention of a phage-immobilized BC biosensor for S. aureus detection is a significant contribution to the field, highlighting the biosafety and efficiency of BC in pathogen identification and demonstrating BC's versatility across multiple sensing platforms. Palladium nanoparticle-bacterial cellulose hybrid nanofibers show excellent electrocatalytic activity for dopamine detection, whereas Au-BC nanocomposite biosensors show efficacy in glucose detection, with potential therapeutic applications. The “lab-on-nanopaper” device, utilizing BC nanopaper, not only visually detects human serum albumin but also establishes itself as a new-generation optical biosensing platform with superiority over conventional substrates. This review contributes to the ongoing advancements in biosensor technology, highlighting the potential of BC as a versatile material for developing innovative biosensors. This is crucial for improving the accuracy, sensitivity, and efficiency of diagnostic tools in healthcare.